The Binding Power of Prenuptial Agreements in the Perspective of the Indonesian Civil Code and Jurisprudential Developments - Basri Basri (PT. Anagata Sembagi Education, 2025)
This study explores the legal strength and enforceability of prenuptial agreements under the Indonesian Civil Code (KUH Perdata) and examines how jurisprudential developments, particularly the Constitutional Court’s Decision No. 69/PUU-XIII/2015, have shifted the legal landscape. Historically, prenuptial agreements were only recognized if executed before marriage, limiting legal protection for couples facing economic, personal, or property changes after marriage. Through a normative juridical approach supported by case analysis, this research reveals that the Constitutional Court’s decision has expanded the legal understanding of contractual freedom by allowing postnuptial agreements. Despite this progressive development, the implementation remains uneven due to inconsistencies in judicial interpretations, absence of procedural regulations, and social stigmas surrounding such agreements. The study concludes that a harmonized legal and administrative framework is necessary to ensure consistent enforcement and public acceptance. Prenuptial and postnuptial agreements, if properly regulated and socially acknowledged, can serve as important instruments for protecting individual rights and maintaining legal certainty in marital relationships.